1998
DOI: 10.1177/002580249803800309
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs of Remand Prisoners

Abstract: A needs assessment protocol which examines 11 problem areas was devised. This was administered to 277 prisoners on remand at Brixton Prison. We found high levels of unmet need for housing, treatment of substance abuse and neurotic symptoms. Twenty-nine per cent were transferred to hospital under the provisions of the Mental Health Act and about a third of those at liberty to do so complied with a discharge plan. Diversion and discharge planning can potentially meet the unmet needs of remand prisoners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The majority of those with alcohol or drug misuse/dependence problems were given a prison sentence (Table 2). Recent data from UK prisons show that approximately 60% of male prisoners and almost 40% of female prisoners were alcohol misusers [24] and 52% of remand prisoners had a need for treatment of their substance misuse [25]. Over recent years the prison service has established drug treatment services, including detoxification and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of those with alcohol or drug misuse/dependence problems were given a prison sentence (Table 2). Recent data from UK prisons show that approximately 60% of male prisoners and almost 40% of female prisoners were alcohol misusers [24] and 52% of remand prisoners had a need for treatment of their substance misuse [25]. Over recent years the prison service has established drug treatment services, including detoxification and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Brooke et al, 1996;Gunn, Maden, & Swinton, 1991;Hardie, Bhui, Brown, Watson, & Parrott, 1998;Brooker et al, 2008); but importantly also add specific detail about the broad range and complexity of needs that these prisoners can and do present to services with, thus providing treating clinicians with a potentially useful clinical focus for further assessment and/ or intervention in the prison setting. Further exploration of unmet needs in the study groups revealed significant differences between HCC prisoners and MSU inpatients on six out of the possible 25 need areas.…”
Section: Psychology Crime and Law 737mentioning
confidence: 99%
“…Measures have been developed and standardized which systematically assess individual needs. Hardie, Bhui, Brown, Watson and Parrott (1998) applied a needs assessment protocol based upon the MRC Needs for Care Assessment to examine 11 problem areas of remand prisoners referred to the healthcare centre at HMP Brixton. Needs are conceptualized differently in each of the instruments.…”
Section: Individual Needs Assessment Instruments Developed In the Nhsmentioning
confidence: 99%